Developing the prosocial entrepreneur - O'Callaghan, Maureen; Robinson, Michelle (Emerald Publishing Limited, 2025)
Developing the Prosocial Entrepreneur critically examines the current unsustainable business model of entrepreneur education and training that often prioritises unlimited growth and consumption and does not consider the negative impacts business decisions have on our health and the environment. The research underpinning this book shows that business owners want to know how they can use their entrepreneurial skills to ensure progress for themselves, the business, and society at a meaningful level. The book will enable business trainers and coaches to help their business owner clients imagine what a sustainable business and society would look like. This in turn will help create opportunities for business owners to develop the knowledge and skills that will enable a more ethical and sustainable way of doing business. The book calls for a shift in mindset from "business as usual" to a more sustainable and inclusive approach.
Includes index.
Keywords: Entrepreneurship.; Business & Economics -- Entrepreneurship.; Entrepreneurship, Start-ups.; elektronické knihy; electronic books